Does Multilingualism Contribute Positive Effects to Student's Self Identity? - Latiff Azmi, Mohd Nazri (2013)
This case study of a qualitative research deals with a group of Malay primary school students who go schooling at vernacular (Chinese) schools in a state of Malaysia. The importance of multilingualism and multicultural aspects is the main focus of the research which aims to investigate on how the students maintain their Malay self-identity. The study also seeks to find the contributing factors of maintaining or losing the self-identity due to the different racial environment. In order to accomplish this sociolinguistic research, fifty eight Malay primary school students were involved in eight Focus Group Discussions, at the same time; twenty four language teachers were involved in in-depthinterviews. In and outside class observations were also used to help the researcher understand the challenges faced by the students and their academic performances were also scrutinized in order to investigate the relevancy of the variables. The study reveals some findings which closely related to sociolinguistic aspects which show that the students have to sacrifice their first language in order to master the targeted language i.e. Mandarin. They have a strong belief that although they have sacrificed a lot of time and effort in mastering the target language, they try their best to improve and uphold their Malay self-identity.